Sums of finite products of Chebyshev polynomials of the second kind and of Fibonacci polynomials - Taekyun Kim; Dae San Kim; Dmitry V. Dolgy; Jin-Woo Park (Journal of Inequalities and Applications, 2018)
Abstract In this paper, we consider sums of finite products of Chebyshev polynomials of the second kind and of Fibonacci polynomials and derive Fourier series expansions of functions associated with them. From these Fourier series expansions, we can express those sums of finite products in terms of Bernoulli polynomials and obtain some identities by using those expressions.